1998
DOI: 10.1177/0021955x9803400604
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure of the Hard Segments in Flexible Foams

Abstract: The main basis of structure-property-relationships of polymeric materials is a good characterization of the structure under study. Such is the case for cross linked polyurethanes such as flexible foams. To overcome the problems of solubility of these materials, a selective degradation process was used, leaving the hard segments unaffected. These were then analyzed by MALDI-TOF (Matrix Assisted Laser Desorption-Ionization Time of Flight mass spectrometry). Using these techniques, the length distribution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…That it is possible to characterize the molecular structure of the hard segments of the polyurethane foams widely used in the automotive industry with respect to chain length distribution and end groups has been demonstrated in the authors' lab [91]. It was found that the length of the the hard segments decreases much more slowly for polyester foams than for polyether foams.…”
Section: Some Selected Examples Of Maldi-ms Application To Non-standamentioning
confidence: 92%
“…That it is possible to characterize the molecular structure of the hard segments of the polyurethane foams widely used in the automotive industry with respect to chain length distribution and end groups has been demonstrated in the authors' lab [91]. It was found that the length of the the hard segments decreases much more slowly for polyester foams than for polyether foams.…”
Section: Some Selected Examples Of Maldi-ms Application To Non-standamentioning
confidence: 92%
“…[1][2][3] The ability of MALDI TOF MS to monitor the molecular-weight distribution of synthetic polymer samples makes the technique useful for identifying the chemical composition and end-functional groups of polymer samples. [4][5][6] MS techniques have been mainly applied to the investigation of polymer segments, prepared by the hydrolysis of high-molecular-weight polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The noted differences in the behaviour of PPU-E-35-0.8 and PPU-75 during climatic ageing are due primarily to the difference in their structure and to the effect of hydrolytic degradation of polyurethanes, fragments of which have different stability [19][20][21][22][23][24][25]. In particular, in terms of susceptibility to hydrolytic degradation, the main fragments of polyurethane foam macromolecules can be placed in the following order: ester > allophanate > biuret > urea > urethane > ether.…”
Section: Resultsmentioning
confidence: 99%